Participant expectations and experiences of a tailored physiotherapy intervention for people with Parkinson's and a history of falls. Issue 5 (27th February 2022) - Rowsell, Alison; Ashburn, Ann; Fitton, Carolyn; Goodwin, Victoria A.; Hulbert, Sophia; Lamb, Sarah E.; McIntosh, Emma; Nieuwboer, Alice; Pickering, Ruth; Rochester, Lynn; Chivers-Seymour, Kim; Ballinger, Claire
Abstract: Purpose: People with Parkinson's are twice as likely to fall as older people within the general population. This longitudinal qualitative study was part of a larger programme of research including a randomised controlled trial to test the effectiveness of a tailored physiotherapy intervention. Specific qualitative aims focused on a subsample of trial participants in the intervention arm of the trial, and comprised the following: To explore the expectations of participants about the intervention. To investigate participants' experiences of the intervention, and its perceived impacts. To understand the facilitators and barriers to engagement. Methods: Two semi-structured interviews were completed with a theoretical sample of people with Parkinson's from the intervention arm, initially after randomisation but before the intervention commenced, and then again six months later. Results: Forty-two participants out of a large clinical trial were interviewed initially, with 37 agreeing to a second interview at six months. Prior experience of rehabilitation plus information accessed through the trial consent procedure informed participants' realistic expectations. Most found the level of the intervention acceptable, and perceived a range of benefits. However, views about equipment provided were more equivocal. The biggest barriers to participation were time and motivation, whilst social support facilitated engagement with the intervention. Conclusions: This study is the first to capture expectations about participation in a programme of exercises and strategies. It highlights that previous challenges to engagement in physical exercises and activities are not a barrier to future participation and provides new insights into the role of equipment and technology in programmes of physical activity for people with Parkinson's. The challenge of ensuring that programmes of exercise and strategies become an embedded feature of everyday life is highlighted, particularly alongside busy social engagements and leisure pursuits. Implications for rehabilitation: For people with Parkinsons, a programme of exercises and strategies has the potential to reduce the risk of falls amongst those with a history of falling. Adherence to such programmes can prove challenging for a variety of reasons, even when participants have realistic expectations about the commitment and effort needed. Clear explanations about the role of equipment and technology within such programmes could enhance adherence. In order to further individualise programmes of exercise for people with Parkinsons, choice regarding social support, reminders and integration into everyday activities should be explored.